The Broken Roof - Hunt,Roderick; illustration, ALex Brychta (Oxford University Press, 1987)
"The Broken Roof" is a book from the Oxford Reading Tree series, designed for young readers. The story centers around the characters as they face the challenge of repairing a broken roof. The roof has been damaged, and the characters work together to figure out how to fix it. Throughout the story, the characters use problem-solving skills, teamwork, and creativity to tackle the issue. The book focuses on the importance of cooperation and determination when dealing with a difficult task. It also encourages children to think about practical solutions to everyday problems. Overall, "The Broken Roof" is an engaging and educational story that combines adventure with lessons in responsibility and teamwork. It highlights how working together can lead to success and how challenges can be overcome with effort and perseverance
Keywords: English reading book